Were Financial Flows in Latin America and the Caribbean Shifted by their Crises?. (25th September 2014) - Delbianco, Fernando Andrés; Fioriti, Andrés
Abstract We study in this paper the presence of structural breaks in the capital flows of 16 economies of Latin America using a unit root test. This is complemented with a specific test of structural breaks and another unit root test. Afterward we proceed to analyze the likelihood of contemporaneity between the breaks found and the crises the countries had suffered in the last 40 years. These crises were either of currency, banking, domestic and external debt type. We find many cases of contemporaneity, especially with the crises that occurred at the end of the 90s. Copyright © 2014 John Wiley & Sons, Ltd.